Renal Cell Carcinoma Update: News from the AUA, EAU, and ASCO Annual Meetings 2011. (22nd March 2012) - Schrader, Andres Jan; Steffens, Sandra
Abstract : Renal cell carcinoma (RCC) is one of the most important urologic malignancies with a continuously growing incidence and health economic relevance. In 2011, several hundred articles, abstracts, and lectures have been presented at the leading global urooncologic congresses. This review was composed to give an overview on the flood of novel findings dealing with diagnostics and therapy of both localized and advanced RCC. The most clinically relevant data are discussed in detail.